Evaluation of the effect of formic acid and sodium formate on hair reduction in rat - Banihashemi M; Khajavi Rad A; Tabatabaee Yazdi SA; Rakhshande H; Masheyekhi Goyonlo V; Zabihi Z; Yousefzadeh H (Dove Medical Press, 2011)
Mahnaz Banihashemi1,2, Abolfazl Khajavi Rad2, Seyed Abbas Tabatabaee Yazdi2, Hasan Rakhshande2, Vahid Mashayekhi Ghoyonlo1,2, Zahra Zabihi3, Hadis Yousefzadeh41Research Center for Skin Diseases and Cutaneous Leishmaniasis, Ghaem Hospital, 2School of Medicine, Mashhad University of Medical Sciences (MUMS), Mashad, Iran; 3Neishabour Medical University, Neishabour, Iran; 4Young Researchers Club, Islamic Azad University, Mashhad Branch, Mashhad, IranAbstract: Hirsutism is a common problem in dermatology that imposes high socioeconomical costs on medical care. Consequently, researchers are actively searching for cheaper and safer methods for therapeutic treatment. The objective of the present study is to evaluate formic oil, enriched from formic acid, for the removal of unwanted hair. In this study, 32 female rats (150–200 g) were randomly divided into four groups and maintained with normal water and food availability. A patch of skin was shaved on each rat for application of test solutions. The control group was treated with local once-daily applications of normal saline. The formic acid, acetic acid, and sodium formate groups were treated with once-daily applications of formic acid (pH 5.5), acetic acid (pH 5.5), or sodium formate, respectively. After 2 weeks, horizontally cut sample biopsies were removed, and the numbers of hair follicles were counted under high field microscopy by a specialist blinded to the treatments. Kolmogorov–Smirnov test results indicated a nonparametric distribution for the rat groups. ANOVA analysis indicated no statistically significant differences between groups (P < 0.05). There weren't any side effects or evidence for toxicity during the study period. However, hair follicle counts showed a descending order of control, acetic acid, formic acid, and sodium formate. Although the sodium formate group had the lowest hair follicle numbers, the difference was not statistically significant (P > 0.05). Formic acid was not effective in reducing hair follicle numbers in rats.Keywords: hair removal, hirsutism, hair follicles